1972
DOI: 10.1007/bf02533243
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of ethanolamine‐ and choline‐containing plasmalogens in adipose tissue

Abstract: Analysis of phospholipids in porcine, bovine and rat adipose tissue revealed a relatively high level of plasmalogens (O‐alk‐1‐enyl lipids). About 50% of the ethanolamine phospholipids in the pig and beef samples consisted of alk‐1‐enylacylglycerophosphorylethanolamine, and the corresponding value for the rat sample was near 35%. In the ethanolamine and choline phospholipid fractions, theO‐alk‐1‐enyl moieties were almost exclusively 16∶0, 18∶0 and 18∶1, whereas the acyl moieties had chain lengths ranging from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1975
1975
1992
1992

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…increase in sphingomyelin. The composition of adipose tissue differs quite markedly from that of normal muscle and is similar to that reported for adipose tissue of other species (Grigor, Moehl and Snyder, 1972) and for microsomes from human connective and adipose tissue (Takagi et al, 1968), particularly with respect to the lower level of choline phosphoglyceride and the much higher proportion of sphingomyelin. Cardiolipin is found mainly in mitochondria and its concentration would be very low in adipose tissue: the phosphorus eluted from the chromatogram in this area must be contributed by another phospholipid, possibly phosphatidic acid.…”
Section: Musclesupporting
confidence: 78%
“…increase in sphingomyelin. The composition of adipose tissue differs quite markedly from that of normal muscle and is similar to that reported for adipose tissue of other species (Grigor, Moehl and Snyder, 1972) and for microsomes from human connective and adipose tissue (Takagi et al, 1968), particularly with respect to the lower level of choline phosphoglyceride and the much higher proportion of sphingomyelin. Cardiolipin is found mainly in mitochondria and its concentration would be very low in adipose tissue: the phosphorus eluted from the chromatogram in this area must be contributed by another phospholipid, possibly phosphatidic acid.…”
Section: Musclesupporting
confidence: 78%
“…The phospholipids from skeletal muscles are particularly rich in ethanolamine plasmalogens, and these will undergo acid hydrolysis during the methylation process to produce the DMA derivatives of hexadecanal and octadecanal. Grigor et al (1972) and Gardner et al (1972) reported the presence of similar concentrations (3-4%) of DMA derivatives of hexadecanal and octadecanal in the fatty acid phospholipids isolated from broilers.…”
Section: Results and Discussion Composition Of Broiler Meat Lipidsmentioning
confidence: 94%
“…These results suggest the presence of small amounts of neutral and phosphatide plasmalogens, respectively, in the neutral and phospholipid fractions (Mangold, 1969). These plasmalogens contain long chain aldehydes (C 16 , C 18 ) bound as enol ethers (Grigor et al, 1972). On hydrolysis, along with methanolysis under acidic conditions, they produce stable dimethylacetal (DMA) derivatives of aldehydes (Wood, 1983;Crackel et al, 1988).…”
Section: Resultsmentioning
confidence: 99%